Carbon-negative emissions: Systemic impacts of biomass conversion: A case study on CO2 capture and storage options. (June 2016) - Hetland, Jens; Yowargana, Ping; Leduc, Sylvain; Kraxner, Florian
Highlights: The paper discusses and compares the efficacy of converting agricultural residues to electricity in power cycles using CCS. The study reveals significant advantages of co-firing schemes as compared to independent biopower systems (BECCS). To provide the same amount of net electric energy, a BECCS plant must burn 30–90% more biomass than a co-fired plant (dependent on size and complexity of the plant). Abstract: This paper is a contribution to the ongoing debate on carbon-negative energy solutions. It deals with biomass conversion in dedicated biopower plants equipped with CCS (BECCS), or co-fired plants retrofitted with CCS in order to generate negative CO2 -emissions. In this context, bioenergy refers to the use of biomass to generate electricity (i.e. biopower) in compliance with the needs of nations and regions without seasonal space heating demand. In this paper, direct-fired and co-fired systems will be addressed, combined mainly with post-combustion flue gas cleaning. The question is which CCS alternative should be preferred in order to obtain negative emissions: either building multiple smaller biopower units, or employing co-firing of biomass and coal in existing large coal power plants. Based on efficacy and the potential for mitigating greenhouse gas emissions as key indicators, some major differences between the alternatives are shown. In the event that a coal power plant equipped with CCS is readily available, more net electric energy (in MWh) can be provided from the feedstock of biomass than would be obtainable from an independent BECCS plant, although the amount of CO2 captured and stored from the biomass (per tonne) will be essentially the same. Further case-specific cost-benefit analyses will be required to determine the feasibility of carbon-negative energy solutions. Although the study is carried out from the perspective of actual biomass sources as regards biomass composition and available technology (i.e. expected efficiency levels) using Indonesian agricultural residues, its main conclusion is fairly general.